The Motive of Passage as a Cultural Universal In I.S. Shmelev’s Novel “The Story of a Love”: Semantic and Functional Aspect - Kondratyeva, Viktoriya (Slavica, 2021)
The article considers the motive of passage from the point of view of its role in the plot inI.S. Shmelev’s novel and from the point of view of mythopoetic meanings. It has been established that in the work “The Story of a Love” the symbolism of the passage motive is associated not only with the situation of the transition, but also with the Fall, which is interpreted by the writer as a stage of the movement towards insight. The passage motive organizes two spaces of storytelling: real and mental. Real space is divided into a space of purity and sin, the transition from one spatial locus to another also signifies the transition taking place in the soul of the protagonist from purity to sin and vice versa. The motives of the passage and temporary death are combined with the Christian motive of the transformation, allowing I.S. Shmelev to show the spiritual toss of the main character more clearly – as a transfer from life to death and its subsequent revival, as well as to assert the main motivein his work – the merger of the “mundane” and the “heavenly”, the world of objects, the material world and the “invisible" world of divine light.